Analisis Sumber dan Jenis Pembiayaan Pendidikan Islam - Ekrita Yanova; Hamdi Abdul Karim (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the sources and types of financing for Islamic education in Indonesia. The method used is a literature review with a qualitative approach through a systematic review of journal articles, scientific books, policy reports, and relevant official documents. Inclusion criteria include literature sources discussing Islamic education financing, Islamic financial instruments, and education financing policies in Indonesia published in the last ten years and possessing conceptual and empirical relevance. Meanwhile, exclusion criteria include sources that do not focus on Islamic education, lack methodological clarity, or are opinionated without adequate academic basis. Data analysis was conducted using content analysis techniques by grouping and interpreting findings based on the source and type of financing. The results of the study indicate that Islamic education financing comes from the government through the APBN/APBD, BOS, and PIP; the community in the form of voluntary donations; parents through personal financing; and Islamic financial instruments in the form of zakat, infaq, sedekah, and waqf (ZISWAF). The types of financing are classified into direct costs, indirect costs, personal costs, and social costs. The research findings confirm that effective, efficient, transparent, and accountable financing management is crucial for improving the quality and sustainability of Islamic education.